AN INNOVATIVE ERECTION TECHNIQUE FOR REDUCING TWO- THIRD OF CONSTRUCTIONAL BRIDGE DEFLECTIONS - Darwish, Ala’a M.; Abdul-Hussein, Wameedh G.; Salman, Nawal D. (European Scientific Journal, ESJ, 2013)
When it is required to cast a bridge over a valley, a river or a busy highway, it is difficult to use the required shoring for the concrete casting molds. In such cases, the heavy weight of fresh concrete will be directly subjected to the bridge. This situation will apply severe stresses to the bare supporting -normally long span- girders, leading to an un-favorite and uncorrectable permanent deflection. In this research, a simple test was done to simulate the mentioned critical case. It was found that; segmental casting of a bridge deck slab can reduce its final deflection. The method was done by casting the intermediate portion of the bridge, then after attaining its hardening another deck slab portion can be casted. The repetition of this process until reaching both ends of the bridge can provide it with extra strength due to the positive properties of the composite action of the hardened concrete. The result of the suggested method is a reduction of two- third of the un- favorite constructional bridge mid span deflection.